2020
DOI: 10.12659/msm.924040
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Probiotics against Esophagogastric Variceal Rebleeding in Patients with Liver Cirrhosis after Endoscopic Therapy

Abstract: Background Probiotic therapy has been shown to be beneficial against some liver diseases. However, there is still uncertainty regarding the clinical efficacy of probiotics for the treatment of variceal rebleeding. This research explored the efficacy of probiotics in variceal rebleeding. Material/Methods This was a retrospective study of 704 consecutive patients with liver cirrhosis who recovered from esophagogastric variceal bleeding after endoscopic treatment. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…In the present study, probiotic users benefited significantly, especially patients with CTP B and C classes. A similar effect of probiotics use was demonstrated in our previous study in patients with cirrhosis (Zhang et al, 2020b). The MELD score is a parameter of a liver function used to assess the prognosis of patients with cirrhosis (Bernardi et al, 2011).…”
Section: Discussionsupporting
confidence: 80%
“…In the present study, probiotic users benefited significantly, especially patients with CTP B and C classes. A similar effect of probiotics use was demonstrated in our previous study in patients with cirrhosis (Zhang et al, 2020b). The MELD score is a parameter of a liver function used to assess the prognosis of patients with cirrhosis (Bernardi et al, 2011).…”
Section: Discussionsupporting
confidence: 80%
“…Faisal et al 38 found that an increased INR value can accurately predict early recurrent bleeding after ligation. Zhang et al 39 used a Cox proportional hazards regression model in a study on the correlation between probiotics and recurrent bleeding of EGVB in cirrhosis, and found that the INR was an independent risk factor for recurrent bleeding within 1 year (HR: 1.697). Our study also concluded that the INR is an independent risk factor for recurrent bleeding within 1 year (HR: 1.294).…”
Section: Discussionmentioning
confidence: 99%
“…Since gut microbiome alterations correlated with the severity, prognosis, and several complications of cirrhosis (Soléet al, 2021), probiotic therapy, which improves the composition of gut microbiota, has been increasingly studied in patients with liver cirrhosis in recent years (Pereg et al, 2011). Probiotic-assisted therapy can reduce variceal rebleeding events in cirrhotic patients and delay the occurrence of rebleeding after endoscopic therapy (Zhang et al, 2020). In addition, probiotics are recommended as a primary treatment for patients with hepatic encephalopathy (Agrawal et al, 2012;Lunia et al, 2014), as they could markedly improve the prognostic outcome of patients presenting with decreased Child-Pugh and Model for End-Stage Liver Disease (MELD) scores (Dhiman et al, 2014).…”
Section: Introductionmentioning
confidence: 99%